IMPLEMENTATION OF KHIYAR IN PURCHASING TICKETS ON THE TRAVELOKA, TIKET.COM, AND BOOKING.COM APPLICATIONS - Rahmawati, Annisa; Lusyana, Dina; Putri, Monica; Bahtiar, Raisa; Suherman, Sabila; Karuniawan, Setya; Falikhatun (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2023)
Khiyar is the right to continue or cancel the sale and purchase contract. Where today's technological developments are very necessary to protect the rights of both parties in carrying out transactions. This research aims to analyze the application of khiyar in purchasing tickets on the traveloka, tiket.com, and booking.com applications. The data used in this research is secondary data taken from books, the official websites of each platform and previous research journals. This research uses a qualitative descriptive method by analyzing the characteristics of the transportation ticket buying and selling transaction process on each platform. Each transaction stage is depicted using a flow chart and the flow is described. Every online transportation ticket purchase transaction is analyzed to determine the implementation of khiyar rights on each platform. The results of this research show that online transportation ticket purchase transactions on the Traveloka, Tiket.com and Booking.com platforms have implemented khiyar ta'yin, khiyar conditions, and khiyar naqd, while khiyar aib is applied on the Tiket.com platform. The results of the khiyar are carried out in accordance with the khiyar provisions between the seller and the buyer.